Tanaidacea from Brazil. I. The family Tanaellidae Larsen & Wilson, 2002 - Larsen, Kim; de L. Araújo-Silva, Catarina; Coelho, Petrônio Alves (Zootaxa, 2009)
Both male and female of two new species, i.e. Araphura arvedlundi n. sp. and Tanaella kroyeri n. sp. were collected from the continental slope of the Atlantic coast off northern Brazil and are described. This is the first record of the male of Araphura. An updated key is given to genus Araphura. Araphura io is transferred to the genus Araphuroides.